Are there rational speculative bubbles in the Philippine stock market? - Nartea, Gilbert; Bo, Hu; Baiding, Hu (2013)
ASEAN stock markets have experienced episodes of long price run-ups followed by large drops over the past 20 years. These apparent bouts of boom and bust have prompted the popular press to conjecture the presence of speculative asset bubbles in these markets causing stock prices to deviate from fundamental values. We use descriptive statistics and McQueen and Thorley’s [1994] duration dependence test to examine the presence of rational speculative bubbles—a special case of speculative bubbles—in the Philippine stock market over the period from 1991 to 2009. We do not detect the presence of rational speculative bubbles in the Philippines using both monthly and weekly returns. This implies that the long run-ups in prices and the subsequent drops over the sample period could have been justified by fundamental value changes. However, it is also possible that there were bubbles caused by irrational investor behavior. We suggest that further research in this area is warranted.
Keywords: Philippine Stock Exchange; Speculation; Stocks -- Prices